Adsorption of commercial dyes using chemically modified biochars derived from empty fruit bunches - Gunasekaran, Sarmila; Abd Wahid, Samsuri; Mohd Izuan Effendi, Halmi (Malaysian Institute of Chemistry, 2022)
In this study, the adsorption capacities of activated empty fruit bunch biochar (EFBB) (an oil palm industry byproduct that is converted into biochar) for methylene blue (MB) and direct red 80 (DR 80) commercial dyes were evaluated. The EFBB was chemically modified by treating it with sulphuric acid (H2SO4), potassium hydroxide (KOH) or iron chloride (FeCl3) to produce acid-treated biochar (A-EFBB), alkali-treated biochar (B-EFBB) and iron-coated biochar (Fe-EFBB). The characteristics of EFBB, chemically modified EFBB and activated carbon (AC) were determined. These adsorbents were used to remove the cationic MB and anionic DR 80 dyes at different initial concentrations and their adsorption capacities were compared. The Langmuir model fitted the isotherm data better than Freundlich’s model, which indicated that adsorption was homogeneous and monolayer. Results for MB showed that the adsorption capacity was in the order: A-EFBB (125 mg/g) > B-EFBB (76.34 mg/g) > Fe-EFBB (10.13 mg/g) > EFBB (6.14 mg/g). For DR 80, the results showed that the adsorption capacity was in the order: B-EFBB (78.13 mg/g) > A-EFBB (40.16 mg/g) > Fe-EFBB (4.71 mg/g) > EFBB (1.15 mg/g).